Innate and germline immune memory: specificity and heritability of the ancient immune mechanisms for adaptation and survival - Boraschi, Diana; Toepfer, Elfi; Italiani, Paola (Frontiers in Immunology, 2024)
The immune memory is one of the defensive strategies developed by both unicellular and multicellular organisms for ensuring their integrity and functionality. While the immune memory of the vertebrate adaptive immune system (based on somatic recombination) is antigen-specific, encompassing the generation of memory T and B cells that only recognize/react to a specific antigen epitope, the capacity of vertebrate innate cells to remember past events is a mostly non-specific mechanism of adaptation that is considered as "innate memory". Innate memory can be considered as germline-encoded, both because its effector tools (such as innate receptors) do not need somatic recombination for being active. Also, in several organisms the memory-related information is integrated in the genome of germline cells and can be transmitted to the progeny for several generations and maintained, but it can also be erased depending on the environmental conditions. The concept of innate immunity being non-specific needs to be revisited, as a wealth of evidence suggests a significant degree of specificity both in the primary immune reaction and in the ensuing memory-like responses. This is clearly evident in invertebrate metazoans, with both non-specific (immune enhancement) or specific (immune priming) memory-like responses. In mammals, there is evidence that some degree of specificity can be attained in different situations, for instance as organ-specific protection rather than microorganism-specific reaction. Thus, innate memory can be non-specific but also specific, can be integrated in the germline and transmitted to the progeny or be short-lived, thereby representing an exceptionally plastic mechanism of defensive adaptation.